PERLINDUNGAN HUKUM TERHADAP KONSUMEN TIMESHARE - Danu Saputri, I Dewa Ayu; Oka Parwata, A. A. Gde (Kertha Semaya : Journal Ilmu Hukum, 2013)
Timeshare is a tourist program where members can join for resort accommodation exclusively for a certain period as long as 20 to 50 years. Sometimes in a Timeshare transaction involving two different parties citizenship. The contract for timeshares is usually made in the English language. As a result a lot of information that is not obtained by consumers when signing a timeshare contract.Therefore, a normative study titled “Legal Protection for Timeshare’s Consumer” has been conducted. This normative research collected through literature study with a card system method. The study aimed to examine the legal protection for the consumer. This study shows that Government needs to make a law to regulate the timeshare business. The best option to make a legal protection in this business is from the contract.
Keywords: Consumer, Legal Protection, Timeshare, Contract business